2014
DOI: 10.3109/14767058.2014.880881
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacterium gleum – a novel bacterium species detected in neonatal respiratory tract infections

Abstract: We report three patients with early neonatal infections. All patients had respiratory tract involvement with increased inflammation markers. Chryseobacterium gleum was cultured from the stomach content aspirated on arrival at the Neonatal intensive Care Unit and it was identified with the help of a Microflex™ MALDI Biotyper mass spectrometer (Bruker-Daltonik, Fremont, CA). Recovery could be achieved with ciprofloxacin treatment. We consider our cases a possible new clinical presentation of a rare human pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…C. gleum is an unusual human pathogen that has been reported as the cause of early neonatal respiratory infection in three neonates [3]. The most common species causing human disease is F. meningosepticum followed by C. indologenes and C. gleum [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. gleum is an unusual human pathogen that has been reported as the cause of early neonatal respiratory infection in three neonates [3]. The most common species causing human disease is F. meningosepticum followed by C. indologenes and C. gleum [10].…”
Section: Discussionmentioning
confidence: 99%
“…Chryseobacterium is typically found in soil, water, plants, and food products and can survive in hospital environments, chlorinated water, and wet surfaces, all of which serve as potential reservoirs of infection. A literature search revealed only a few published cases in countries including Hungary, India, Croatia, and Saudi Arabia [36]. In Senegal, two cases of meningitis due to Flavobacterium meningosepticum were diagnosed in the late 1970s [7] as well as one case of Chryseobacterium indologenes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Leggyakrabban a C. gleum és C. indologenes fajok fordultak elő az elemzett mintákban. Érdemes megjegyezni, hogy a C. gleumot újszülöttek alsó légúti fertőzéseiben is leírták kórokozóként [11]. Esetleírásban számoltak már be COPD-s beteg kórházi előzmény nélküli C. indologenes-pneumoniájáról [12].…”
Section: Fontosabb Ritkábban Előforduló Gram-negatív Pálcák Jellemzéseunclassified
“…Patients at both extremes of age and immunocompromised individuals are more susceptible to this infection (6,7). Very limited clinical data are available for this newly identified pathogen, and it has been rarely reported as a cause of sepsis anywhere in the world (Table 1) (8).…”
mentioning
confidence: 99%
“…Most of the cases of C. gleum infections have been treated successfully with a fluoroquinolone (ciprofloxacin and levofloxacin) or piperacillin-tazobactam (1,6,7). In contrast, Garg et al reported resistance to fluoroquinolones and susceptibility to only tetracycline and minocycline (9).…”
mentioning
confidence: 99%